Increasing Biology Learning Result With Cooperative Learning Type Student Teams Achievement Division (STAD) - Purnawan, Rochadi Arif (Biosfer: Jurnal Pendidikan Biologi, 2014)
Inaccurate selection of learning method is believed to be one of factors causing low learning result on biology subject. This study conducted by action research method was aimed to find out the effect of cooperative learning type Student Teams Achievement Divisions (STAD) on organ systems topic to increase biology learning result of 11th grade sciene student of SMAN 40 Jakarta in the first semester in academic years 2012/2013. Data obtained from cycle one and two showed that the average learning result increased from 73.10% to 85.80% along with the improvement on learning achievement increased from 61% to 94.4%. Increase result of several student activities assessed in the cycle 1 and 2 were also identified. Average percentage of overall student activity was slightly elevated from 75% to 86%. Similarly, better accomplishement in enthusiasm (53% to 92%), willingness to ask (38% to 81%), and team work (81% to 92%). Based on those result, it was concluded that the result of Biology learning on Organ System topic can be increased using cooperative learnig type STAD.